Effect of aging on lower urinary tract symptoms and urodynamic parameters in women - Hui-Hsuan Lau; Tsung-Hsien Su; Wen-Chu Huang (Elsevier, 2021)
Objective: Lower urinary tract symptoms (LUTS) are common in women. However, due to multifactorial etiologies, it is difficult to determine the prevalence, and functional changes with age. The aim of this study is to assess the effect of age on female LUTS, urethral and bladder function after their midlife. Materials and methods: This was an observational cohort study conducted at a tertiary referral medical center. Women who visited for bothersome LUTS, valid quality of life questionnaires, and urodynamic tests were recruited into the this study. Patients The patients were divided into four groups (<50, 50-59, 60-69, and >69 years). All LUTS, and urodynamic parameters were reviewed, and compared between groups. Results: A total of 364 women were enrolled and analyzed. The urodynamic tests showed the that maximal cystometric bladder capacity, the average and maximal urine flow rate, and pressure of detrusor contractility at maximal urine flow rate were all significantly decreased with age. Besides, the voiding time, and post-voiding residual urine volume significantly increased with age. For urethral competence, the maximal urethral closure pressure deteriorated with age. All storage symptoms did not change with age, except for nocturnal enuresis. However, the effect of age on some voiding symptoms significantly increased with age, including straining to void, hesitancy, and intermittency. Conclusions: Lower urinary tract symptoms, bladder and urethral functions change with age, particularly voiding function. Physicians should be aware of the aging process when counseling and before implementing management strategies, particularly for older people.